KETALS OF L-RHAMNOHEPTONOLACTONES - POTENTIAL MIMICS OF L-RHAMNOSE - Wheatley, J; Beacham, A; Lilley, P; Watkin, D; Fleet, G (1994)
Isopropylidene and cyclohexylidene ketals of γ- and δ-heptonolactones derived from Kiliani ascensions of protected L-rhamnose may constitute suitable intermediates for the preparation of mimics of L-rhamnose. The X-ray crystal structure of 7-deoxy-3,4-O-isopropylidene-L-glycero-L-galacto-heptono-1,5-lactone provides an example of a δ-lactone in a boat conformation with a substituent in a flagpole position. The size of ring in the lactones is completely consistent with Hudson's classical lactone rotation rule of 1910. © 1994.